METAL-POLYMER SOLAR COLLECTORS WITH MULTICHANNEL ABSORBER FOR MULTIFUNCTIONAL MULTIPURPOSE ENERGY SYSTEMS - Doroshenko A.; Danko V.; Turbovets Y. (Problems of the Regional Energetics, 2012)
New modification of liquid-metal-polymer solar collector for solar heating and for creation of multifunctional energy systems on its basis, particularly solar refrigeration systems was developed. A comparative study of several modifications of polymer collectors involving data of a set of foreign researchers was made and high efficiency of the new elaboration was proven.